A Hybrid Model for Resolving Customary Land Disputes in Papua’s Indigenous Communities - Wutwensa, Bruri Marwano; Lobubun, Muslim; Rato, Dominikus; Anggono, Bayu Dwi (Jurnal Ilmu Hukum Kyadiren, 2025)
This study examines customary land disputes among indigenous communities in Papua, focusing on the alignment of existing legal mechanisms with the justice values held by these communities. Employing a normative legal approach and socio-legal analysis, this research explores the philosophical, cultural, and legal dimensions of the land, emphasizing its communal and spiritual significance. Findings reveal that Indonesia’s formal legal framework, grounded in individual ownership and state-centric policies, often overlooks indigenous rights, causing unresolved conflicts and cultural disenfranchisement. The research proposes a hybrid dispute resolution model integrating customary practices with state recognition, including specialized customary land tribunals and mandatory consultation processes. This model seeks to bridge the gap between formal and customary laws, promoting equitable dispute resolution and safeguarding the cultural heritage of Papua’s indigenous communities. Recommendations aim to enhance legal recognition and foster sustainable land management in Papua.